Produktivitas Guru Melalui Kepemimpinan Transformasional Dan Lingkungan Kerja di Sekolah Dasar Wilayah Kecamatan Cibarusah: Teacher Productivity Through Transformational Leadership and Work Environment in Elementary Schools in Cibarusah District - Aliy Rasyid; Yanto Lesmana; Sinta Aulia Kusumawati (Jurnal Bisnis dan Ekonomi, 2025)
Abstract:Teacher productivity is a teacher's ability to manage all aspects of their professional duties effectively and efficiently to achieve educational goals. Productive teachers not only fulfill their teaching obligations but are also able to plan lessons effectively, implement meaningful teaching and learning processes, conduct appropriate evaluations, and continuously improve their professional competence. The level of teacher productivity is influenced by various factors, including principal leadership, the work environment, motivation, and infrastructure support.Objectives: The objectives of this study were to determine the level of productivity of elementary school teachers in Cibarusah District. To determine the application of transformational leadership by principals in elementary schools in Cibarusah District. To determine the work environment conditions of elementary school teachers in Cibarusah District. To determine the effect of transformational leadership on elementary school teacher productivity in Cibarusah District. To determine the influence of the work environment on elementary school teacher productivity in Cibarusah District. To determine how transformational leadership and the work environment simultaneously have a significant effect on elementary school teacher productivity in Cibarusah District.Methodology: The approach chosen for this investigation involved qualitative research methods, given their capacity to facilitate a more comprehensive and in-depth understanding of the subject under examination.Research Results: The study findings indicate that the implementation of a transformational leadership approach significantly improves teacher performance. Furthermore, it is clear that a supportive work environment significantly increases teacher productivity.Keywords: Teacher Productivity, Transformational Leadership, Work Environment, Elementary Schools.